Non-destructive strength testing of microindented float glass by a nonlinear acoustic method - Karlsson, S.; Kozłowski, M.; Grund, L.; Andersson, S. A.K.; Haller, K. C.E.; Persson, K. (Construction and Building Materials, 2023)
The present paper describes a method for non-destructive testing of the glass strength. Square 10 × 10 cm2 samples of annealed float glass was inflicted with a controlled defect in the centre of the atmospheric side using Vickers microindentation-induced cracking with a force of 2 N, 5 N and 10 N and compared to an un-indented reference. The samples were non-destructively tested using a nonlinear acoustic wave method resulting in defect values. The average of the defect values was found to linearly correlate to the indentation force in a log–log relationship. The samples were subsequently tested in a ring-on-ring setup that allows for an equibiaxial stress state. The indentation-induced cracking gave practically realistic strength values in the range of 45 to 110 MPa. The individual sample values for failure stress as a function of normalized defect value show linear trends with approximately half of the data within 95% confidence limit. In summary, this study provides an initial proof-of-concept for a non-destructive testing of the strength of glass.
Keywords: Float glass; Glass strength; Indentation cracking; Microindentation; Non-destructive testing; Nonlinear acoustic wave; Ring-on-ring test